Substituição parcial do farelo de soja e da farinha de trigo pelo farelo de algodão em dietas balanceadas para juvenis de camarão branco, Litopenaeus vannamei - Martins, Rafael Barroso (2014)
Ingredients of vegetable origin are increasingly sought to compose the feeds for farm-reared shrimp. The search for such raw materials generates a large market demand for traditional ingredients that are produced mostly in other regions, raising formula cost. The use of regionally-available ingredients can provide a better return to shrimp farmers in the Northeastern Brazil, the main national producer of farmed shrimp. This study evaluated the growth performance of juvenile Litopenaeus vannamei when fed diets containing cottonseed meal as a partial substitute for soybean meal and wheat flour. L. vannamei juveniles of 1.51 ± 0.05 g were stocked in 500 L tanks at a density of 70 shrimp m-2 for 72 days in a continuous water recirculation and filtering system. A control diet (FA0) was used, containing no inclusion of cottonseed meal. The other diets were prepared to contain cottonseed meal at 3%, 6%, 9% and 12% of the diet. At the end of the study, mean values were evaluated for shrimp survival (%), shrimp final body weight (g), shrimp weekly weight gain (g), shrimp yield (g m- 2), apparent shrimp feed intake (g shrimp-1) and feed conversion ratio. Results showed no statistically significant difference between dietary treatments for all parameters evaluated. These results allow us to conclude that it is possible to reduce the inclusion levels of wheat flour and soybean meal at 17% and 11%, respectively, substituting for a regionally-available ingredient (cottonseed meal), reducing formula costs for feeds of L. vannamei.